2019
DOI: 10.9734/ajee/2019/v9i230088
|View full text |Cite
|
Sign up to set email alerts
|

Composition, Generation and Management Method of Municipal Solid Waste in Addis Ababa City, Central Ethiopia: A Review

Abstract: Municipal Solid Waste management is one of the most fundamental issues in the contemporary urban environments particularly in developing countries like Ethiopia. A huge generation of waste coupled with unbalanced waste management services is the major challenges facing the City of Addis Ababa. A continuous increase of production of more wastes and change in the composition of waste into complex, the waste management practice is challenged by low prioritization of waste management, limited revenues for financin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 36 publications
2
7
0
Order By: Relevance
“…This finding conforms with the study by Tassie-Wegedie [21] The study also pointed out that open dumping is the commonest method of solid waste dumping being practiced followed by landfill. This finding is consistent with earlier study findings by Tassie [23] which reported that open dumping is the most widespread method of solid waste disposal in most urban centres in developing countries and it typically involves the uncontrolled disposal of waste without measures to control leachate, dust, and odours. These results reveal that people yet do not clearly distinguish between the landfill and open dump making them not feel bad.…”
Section: Discussionsupporting
confidence: 93%
“…This finding conforms with the study by Tassie-Wegedie [21] The study also pointed out that open dumping is the commonest method of solid waste dumping being practiced followed by landfill. This finding is consistent with earlier study findings by Tassie [23] which reported that open dumping is the most widespread method of solid waste disposal in most urban centres in developing countries and it typically involves the uncontrolled disposal of waste without measures to control leachate, dust, and odours. These results reveal that people yet do not clearly distinguish between the landfill and open dump making them not feel bad.…”
Section: Discussionsupporting
confidence: 93%
“…However, the amount of waste generated was different from each source. For example, among the total municipal solid waste generation of Addis Ababa, households account for 70%, commercial institutions 9%, industries 6%, hotels 3%, hospitals 1%, street sweepings 10%, and other sources accounted for 1% [51]. This shows that the majority of municipal solid waste generation comes from households.…”
Section: Waste Generationmentioning
confidence: 99%
“…Solid waste collection is one of the main components of municipal solid waste management [51]. In urban areas of Ethiopia, formal solid waste collection is mostly conducted by micro and small enterprises that collect waste door-to-door and transport the waste to facilities and disposal points [39].…”
Section: Waste Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, most of the waste is compostable, 47% ashes, leaves 15.7%, 4.2% vegetables, and the remaining wastes that can be recycled are plastics 2.9%, cardboard and paper 2.5%, metal 0.9%, and glasses 0.5%. Another study conducted by Tassie et al [26] indicates that about 86% of the total waste generated is degradable (easily decomposable). Different studies have shown different compositions of waste in Addis Ababa.…”
Section: The Physical Composition Of Solid Waste In Addis Ababamentioning
confidence: 99%